(3CeGdj GdeMGedjs - (3GdeMGedj, GdVHj, CHh YHO Gddg, GdMSjf Hf ESeGYjd Hf eMeO Hf ESeGYjd, J (B330(3g`s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdZfGFe eMeO Hf Ydj (B... (3Yf YHO GdQMef GdSdej Yf Ydj bGd(B: (3cfG aj LfGRI aj HbjY GdZQbO, bGd(B: (3aCJGfG QShd Gddg Udi Gddg Ydjg hSde abYO abYOfG(B...s
(3BNQgG (B:s
(3MOKfj GHf CHj GdRfGO Yf gTGe Hf YQhI Cf YHO Gddg Hf GdRHjQ jbhd aj (B... (3aj CKQ cd UdGI HYO Cf jSde hbHd Cf jbhe(B: (3dG Edg EdG Gddg(B... (3hcGf CHj EPG UdGI GdecJhHI JfMi Yf eUdGg aSHM(B. (3BNQ GdLRA GdKGdK(B...s
(3QhGjI(B: (3CHj eMeO YHO Gddg Hf YHjO Gddg Hf jMji Hf RcQjGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B234s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs